2009
DOI: 10.1136/ard.2008.102509
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported outcomes improve with etanercept plus methotrexate in active early rheumatoid arthritis and the improvement is strongly associated with remission: the COMET trial

Abstract: Early treatment with ETN+MTX leads to significantly greater improvements in multiple dimensions of PROs than MTX alone. The close relationship between disease activity and PRO improvement suggests that early treatment, with remission as a goal, should maximise the chance of restoring normal functioning and HRQoL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(66 citation statements)
references
References 22 publications
4
60
0
2
Order By: Relevance
“…Numerous randomized clinical studies have found that significantly more patients achieve DAS28 decrease of ≥1.2 and remission when biologic treatment is received within 1 year of diagnosis compared with later [3,4,[22][23][24][25][26][27][28]. This study confirms that the same response is consistently observed in real-world clinical practice in three different countries in Europe.…”
Section: Discussionsupporting
confidence: 87%
“…Numerous randomized clinical studies have found that significantly more patients achieve DAS28 decrease of ≥1.2 and remission when biologic treatment is received within 1 year of diagnosis compared with later [3,4,[22][23][24][25][26][27][28]. This study confirms that the same response is consistently observed in real-world clinical practice in three different countries in Europe.…”
Section: Discussionsupporting
confidence: 87%
“…In this study, leflunomide was associated with the lowest scores of both anxiety and depression [113]. Similarly, Kekow et al reported no significant change in depression scores in patients with early active rheumatoid arthritis treated with etanercept+MTX compared with those treated with MTX only [117]. Despite underlining the importance of future studies in this area, these differences may result from different study designs, as well as different populations and stages/severity of disease.…”
Section: Depression and Rheumatoid Arthritismentioning
confidence: 38%
“…Meta-analysis of RCTs of adjunctive treatment with anti-cytokine therapy Of three trials [48][49][50] that used anti-cytokine drugs as adjunctive treatment, two provided enough data for meta-analysis (Figure 2b). 49,50 Both of these studies compared combination of etanercept and a DMARD (n = 544) with DMARD alone (n = 405).…”
Section: Resultsmentioning
confidence: 99%